2009
DOI: 10.1182/asheducation-2009.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Hb H disease: clinical course and disease modifiers

Abstract: Hemoglobin H (Hb H) disease is the most common form of thalassemia intermedia and has many features that require careful consideration in management. In the majority of cases, Hb H disease results from double heterozygosity for alpha(0)-thalassemia due to deletions that remove both linked alpha-globin genes on chromosome 16, and deletional alpha(+)-thalassemia from single alpha-globin gene deletions (--/-alpha). However, Hb H disease may occur from interactions between alpha(0)-thalassemia with non-deletional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
154
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 27 publications
2
154
0
9
Order By: Relevance
“…For these patients, transfusions may be required from infancy, with eventual splenectomy. 10 Genotyping of 836 thalassemia patients in the United States by the National Institutes of Health Thalassemia Clinical Research Network identified 106 (12.7%) with HbH disease, 46 (5.5%) with a nondeletional ␣ mutation, and 44 with HbH and Hb CS, most of them from the west coast. 11…”
Section: Hbh Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For these patients, transfusions may be required from infancy, with eventual splenectomy. 10 Genotyping of 836 thalassemia patients in the United States by the National Institutes of Health Thalassemia Clinical Research Network identified 106 (12.7%) with HbH disease, 46 (5.5%) with a nondeletional ␣ mutation, and 44 with HbH and Hb CS, most of them from the west coast. 11…”
Section: Hbh Diseasementioning
confidence: 99%
“…1 Nearly 70 different nondeletional mutations exist that may be coinherited with deletional mutations or other genetic modifiers that result in variable genotypic and/or phenotypic expression. 10 A diagnosis of ␣-thalassemia can be suspected based on factors, such as a family history of anemia and geographic and ethnic background, particularly if the patient comes from the Middle East, North Africa, and Southeast Asia, areas where ␣-thalassemia is …”
Section: The ␣-Thalassemiasmentioning
confidence: 99%
“…Subsequently, HbH disease or a-thalassaemia with three out of four affected a-globin genes (--/2a), may cause severe anaemia shortly after birth and may lead to transfusion dependency later in life. 4,5 Especially children with a non-deletional HbH disease (Hb Constant Spring) may have growth delay, severe anaemia during infectious illness and require blood transfusion with consequent iron overload. 6 Early detection of this severe disorder by newborn screening leads to improvement of parental information, allows anticipatory prevention, supportive therapy and treatment in case of infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] It has been shown experimentally that deletion of MCS-R2 alone is sufficient to down-regulate alpha-globin expression to less than 3% of normal, consistent with the notion that MCS-R2 is the most important regulatory element. 8,9 In our patient, the homozygous deletion of MCS-R2 is associated with HbH disease, a phenotype less severe than expected from the predicted reduction of alpha-globin chain expression.…”
mentioning
confidence: 49%
“…Most commonly HbH disease results from deletion or dysfunction of 3 of 4 alpha-globin genes, and rarely from deletions in the upstream regulatory region. 2,[4][5][6] Here we describe a severe case of HbH disease in a 11-year-old Italian boy due to deletions of variable extent of both upstream regulatory regions, with all 4 downstream alpha-globin genes intact. The hematologic characteristics of the proband and his family are reported in Figure 1.…”
mentioning
confidence: 99%